Pengembangan Model Pembelajaran Berbasis Website Menggunakan Moodle System pada Mata Kuliah Teknologi Informasi dan Komunikasi - Gazaly, Muragmi; Rahmawati, Rahmawati; Zainuddin, Zainuddin (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2024)
This research aims to develop a website-based learning model using Moodle for information and communication technology courses, applying the ADEL model learning steps. The study follows an R&D approach using the PPE model, which includes planning, production, and evaluation stages. Data collection involved product assessment instruments for content, construct validity, practicality, and student response questionnaires. Product trials were conducted in limited and large group settings, with 79 students from the Faculty of Tarbiyah and Teacher Training in Southeast Sulawesi, Indonesia. Results indicate that the Moodle-based learning model is suitable for the learning process, demonstrating very good validity and practical criteria. Student responses were positive, showing that the model is both valid and practical for implementation in educational settings.